eV-scale sterile neutrino search using eight years of atmospheric muon neutrino data from the IceCube Neutrino Observatory - Aartsen, MG; Abbasi, R; Ackermann, M; Adams, J; Aguilar, JA; Ahlers, M; Ahrens, M; Alispach, C; Amin, NM; Andeen, K; Anderson, T; Ansseau, I; et al. (American Physical Society, 2020)
The results of a 3+1 sterile neutrino search using eight years of data from the IceCube Neutrino Observatory are presented. A total of 305 735 muon neutrino events are analyzed in reconstructed energy-zenith space to test for signatures of a matter-enhanced oscillation that would occur given a sterile neutrino state with a mass-squared differences between 0.01 and 100  eV^{2}. The best-fit point is found to be at sin^{2}(2θ_{24})=0.10 and Δm_{41}^{2}=4.5  eV^{2}, which is consistent with the no sterile neutrino hypothesis with a p value of 8.0%.